THE CHALLENGES OF THE WORLD OF EDUCATION AGAINST THE DEVELOPMENT OF HUMAN RESOURCES IN ISLAMIC EDUCATION - Sholeh, Lukman; Baharuddin, Baharuddin (Universitas Nurul Jadid, 2022)
This paper focused on challenging the challenges of the world of education in developing human resource management (MSDM) in Islamic education. The methodology or approach used in this paper uses a library research method or approach. At the same time, data collection was carried out by studying or exploring several journals, books, and documents (both printed and electronic) as well as data sources and or other information that was considered relevant to the study; the purpose of this study was to find out the challenges of the world of education in developing resource management humans were educated in Islam, the results of this study concluded that the challenges of the world of education were several aspects 1. the political challenges, 2. the culture Challenges, 3. the science and technology Challenges, 4. the economy Challenges 5. the society Challenges 6. the value systems challenges